Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Inap Di Puskesmas Gondang Sragen - Sari, Sinta Wisma, Dr. Anton Agus Setyawan, MSi, Dr. Syamsudin, MM (2016)
Customer satisfaction has become a central concept in the management of business discourse. Quality is a core survival of an institution. This study aims to investigate the influence of a quality service to satisfaction of inpatients in health centers gondang sragen in 2015. This study used a convenience sampling techniques to determine the number of samples obtained 120 respondents. This study was conducted in November 2015. The validity of the test results obtained on tangible, reliability, responsiveness, assurance, empathy, acces, communication, security and satisfaction have a valid result with a probability value <0.05. And the overall reliability of the results obtained items Cronbach alpha> 0.60, and declared all the items found to be reliable or reliable instrument. On the results of this study indicate the existence of several items the kind of services that affect patient satisfaction in the clinic gondang. Researchers provide advice to management to further improve the quality and service that already exists in the clinic gondang sragen.